2021
DOI: 10.1038/s41598-021-98695-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of head movements tests in force plate and accelerometer based posturography in patients with balance problems due to vestibular dysfunction

Abstract: This study compares HS posturography on inertial sensors (MediPost) with force platform posturography in patients with unilateral vestibular dysfunction. The study group included 38 patients (age 50.6; SD 11.6) with unilateral vestibular weakness (UV) and 65 healthy volunteers (48.7; SD 11.5). HS tests were performed simultaneously on the force plate and with MediPost sensor attached at L4. Four conditions applied: eyes open/closed, firm/foam. The tests were performed twice, with the head moving at the frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The instrumental measurement performed using MediPost mobile posturography localized at the L5 level, assessed postural stability in different conditions where the noted grade of improvement varied, as stated in the literature [ 13 , 39 , 40 , 41 ]. The results of condition 4 (standing on foam, eyes closed) were statistically significant for all MediPost measures, which is consistent with other studies [ 5 , 29 , 42 ]. The results of condition 1 (firm surface, eyes open) and condition 2 (firm surface, eyes closed) are clinically unsatisfactory.…”
Section: Discussionsupporting
confidence: 92%
“…The instrumental measurement performed using MediPost mobile posturography localized at the L5 level, assessed postural stability in different conditions where the noted grade of improvement varied, as stated in the literature [ 13 , 39 , 40 , 41 ]. The results of condition 4 (standing on foam, eyes closed) were statistically significant for all MediPost measures, which is consistent with other studies [ 5 , 29 , 42 ]. The results of condition 1 (firm surface, eyes open) and condition 2 (firm surface, eyes closed) are clinically unsatisfactory.…”
Section: Discussionsupporting
confidence: 92%
“…[35][36][37][38][39][40][41][42][43][44][45][46][47]). The application of computational methods to IMU-based data sets has demonstrated that this method can provide a clinician with a comparable ability to differentiate between individuals with vestibular loss and healthy controls as force platform posturography [48]. Furthermore, machine learning algorithms, which extract important features from IMU data, can be trained to produce estimates of balance performance that are as accurate as those of expert examiners (i.e., trained physical therapists) [49,50].…”
Section: Imu Measures Of Postural Stability and Implications For Vest...mentioning
confidence: 99%
“…Numerous studies have contributed valuable insights into the assessment of balance, underscoring the potential of innovative devices for evaluating vestibular function. Janc et al compared head movement tests using force plate and accelerometer-based posturography, highlighting the ability of both devices to differentiate between patients with balance problems and healthy individuals [13] . Rosiak et al evaluated the utility of the MediPost Mobile Posturography Device in assessing patients with a unilateral vestibular disorder, reporting high sensitivity and specificity in distinguishing between healthy individuals and those with a vestibular deficit [14] .…”
Section: Introductionmentioning
confidence: 99%